COMPARATIVE DESCRIPTION OF POPULATION PARAMETERS OF THE LIFE QUALITY OF INHABITANTS OF DAKHADAEV DISTRICT, REPUBLIC OF DAGESTAN - Patimat Asadullamagomedowna Bekshokova; Patimat Iman-Vazalievna Gabibova; D. I. Kadieva (Юг России: экология, развитие, 2015)
The study presents the population indices of the life quality of inhabitants of Dakhadaev district, Republic of Dagestan. The study was conducted using a questionnaire SF-36. The regularities of the age-and gender changes of parameters of the life quality were identified. The highest rate in the analyzed settlements was marked on a scale of social functioning, the lowest – on the scale of overall health. The integral indexes of men were higher in all age groups than those of women. The highest parameters of the integral index of the male and female population were fixed in the age-group to 35. The most gender differences are noted on the scale of the role-physical functioning, the least on the scale of social functioning. In whole with age increasing we saw lowering parameters of indices of the life quality as in male group, so in female one. Besides the most changes in indices of the life quality were on the scale of role-physical functioning. Minimal differences in age groups were observed on the scales of social functioning and mental health. Women have more age lowering of indices of the life quality than men exceptthe role-physical functioning and social functioning. The highest parameter of the integral index of the life quality was observed in Zilbachi administrative settlement, the lowest one – in Kharbuk settlement of Dakhadaev district, Republic of Dagestan. The data of population study of the life quality give the information about indices of the life quality of population, reflecting in such a way the degree of its physical, psychological and social wellbeing. This information allows to estimate the efficiency of realization different medical and social and economic programs, aiming to improvement of the life quality of the population, rising the level of its wellbeing.Aim. The aim of this work was a pilot study of population indices of the life quality of inhabitants of Dakhadaev district, Republic of Dagestan.Location. Dakhadaev district, Republic of Dagestan.Methods. The study was conducted using a questionnaire SF-36 in accordance with the requirements of the International project of evaluation of life quality (IPELQ). Data was collected by questionnaire on the basis of direct survey respondents. Statistical processing of the data obtained from surveys of the quality of life based on the general principles of statistics and conducted using the package of applied programs STATISTICA and Excel.Results. Population indices of the quality of life of the residents in some rural settlements in Dakhadaev district of Republic of Dagestan were received. Average indicators of the life quality of residents for 8 scales of the questionnaire SF-36 range from 58,5 (scale of the overall health) to 76,3 (scale of social functioning). The study of gender differences in population indices of quality of life showed that the parameters of the life quality of the male population in all scales of the questionnaire significantly higher than those in women. A similar trend was observed in all age groups, that is, in general, indicators of physical, mental and social functioning of the female population of the studied territories were lower than of men. Indicators of the life quality in the analyzed settlements are decreasing in both men and women.Main conclusions. The results of population studies of quality of life in general indicate that the environmental component, understood in the framework of 3-defining model of sustainable development (economy, social sphere, ecology), makes a great contribution to the integral profiles quality of life of the rural population. Although the countryside is traditionally considered to be ecologically safe, in our study the numeric parameters of the quality of life have the same dynamics as in studies of population in large, industrialized cities, reflecting the specific problems of the environment.